Cost effectiveness analysis of a Vertical Midimew-connected Mesh Network (VMMN) - Rahman, M. M. Hafizur; Al Faisal, Faiz; Mohd. Nor, Rizal; Tengku Sembok, Tengku Mohd; Behera, Dhiren Kumar; Inoguchi, Yasushi (Springer, 2017)
Previous study of vertical midimew-connected mesh network (VMMN) has been conducted to evaluate some of static network performance parameters of this network. These parameters include diameter, network degree, average distance, wiring complexity, cost, and arc connectivity. VMMN showed good results compared to some of conventional and hierarchical interconnection networks. However, there are some important static parameters that were not included in that study such as packing density, message traffic density, cost effectiveness factor, and time-cost effectiveness factor. In this paper, we will focus on evaluating VMMN to these parameters, and then we will compare the results to that from mesh, torus, TESH, and MMN networks.